Sex differences in chronic obstructive pulmonary disease characteristics: the Korea National Health and Nutrition Examination Survey 2007–2018 - Moon Seong Baek; Haegwang Shin; Kang-Mo Gu; Hae In Jung; Won Young Kim; Jae-Woo Jung; Jong-Wook Shin; Sun-Young Jung; Jae-Yeol Kim (The Korean Journal of Internal Medicine, 2024)
Background/Aims Chronic obstructive pulmonary disease (COPD) is less prevalent in females than males, but it affects mortality in females. There may be sex differences in the clinical characteristics of COPD. Methods We analyzed the Korea National Health and Nutrition Examination Survey dataset from 2007 to 2018. We compared the clinical characteristics and comorbidities in subjects with COPD according to sex. We adjusted the multivariate logistic regression of lung cancer prevalence according to COPD and sex by age and smoking amount. Results Females with COPD tended to be older than males with COPD (64.1 ± 0.4 yr vs. 62.3 ± 0.2 yr, respectively, p < 0.001). Approximately 89% of males with COPD had a smoking history, while 86% of females with COPD were non-smokers (p < 0.001). Household income was lower (p < 0.001) and asthma and overall malignancy were more prevalent in females with COPD than males with COPD (25.5 vs. 11.6%, respectively, p < 0.001; (6.3 vs. 5.4%, respectively, p < 0.001). However, lung cancer was more common in males with COPD than females with COPD (0.9 vs. 0.1%, respectively, p < 0.001). Lung cancer prevalence increased in males with moderate COPD compared to subjects without COPD (OR, 4.409; 95% CI, 1.741–9.419). Conclusions Females with COPD had a lower smoking rate, household income, and lung cancer prevalence than males with COPD. More active COPD screening is needed for women of low socioeconomic status, even if they do not smoke.